2022
DOI: 10.1111/liv.15183
|View full text |Cite
|
Sign up to set email alerts
|

Haemostatic alterations in patients with cirrhosis and hepatocellular carcinoma: laboratory evidence and clinical implications

Abstract: Venous thrombosis is a frequent complication in cancer and is associated with high morbidity and mortality. Hepatocellular carcinoma (HCC) is the most common primary liver cancer and a leading cause of cancer‐related death worldwide, and it is associated with preexisting cirrhosis in 90% of cases. Patients with cirrhosis acquire complex alterations in their haemostatic system that may predispose them to bleed or thrombotic complications. There is growing evidence that HCC may tilt the haemostatic equilibrium i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 122 publications
0
17
0
1
Order By: Relevance
“…These exclusion criteria were chosen to mitigate the effects of potential confounders on the assessment of hemostasis. [23] , [24] , [25] , [26] , [27] , [28] …”
Section: Methodsmentioning
confidence: 99%
“…These exclusion criteria were chosen to mitigate the effects of potential confounders on the assessment of hemostasis. [23] , [24] , [25] , [26] , [27] , [28] …”
Section: Methodsmentioning
confidence: 99%
“…A meta‐analysis of 11 studies (including both in‐ and outpatient populations) reported an increased risk of VTE with an OR of 1.7 (95% CI 1.3–2.2) associated with cirrhosis 18 . Patients with cirrhosis and hepatocellular carcinoma are at additional risk of VTE 19 with a cumulative incidence of 6% in a single‐center study, which reported hepatocellular carcinoma, multiple lesions, and distant metastases as independently associated with VTE 20 . VTE is associated with increased length of hospital stay and mortality in patients with cirrhosis 12,20,21 …”
Section: Epidemiology Of Ha‐vte In Patients With Cirrhosismentioning
confidence: 99%
“…Other factors that may induce blood hypercoagulability in patients with cirrhosis are systemic inflammation, a well-recognized feature of decompensated cirrhosis [ 51 ], and HCC [ 52 ]. The former is scarcely studied with contradictory results [ 24 , 28 ].…”
Section: Pathophysiology and Risk Factorsmentioning
confidence: 99%
“…No information in this matter was provided in the long-term albumin administration trials [ 54 , 55 ]. As far as HCC is concerned, there is growing evidence suggesting that it is associated with pro-thrombotic alterations (i.e., increased platelet activation and function, enhanced thrombin generation, hypo-fibrinolysis, and elevated levels of prothrombotic microvesicles) that may synergistically contribute to hypercoagulability and thrombosis [ 52 ].…”
Section: Pathophysiology and Risk Factorsmentioning
confidence: 99%